Research on Medium and Long-Term Runoff Forecast of Xijiang River in Dry Season Based on Statistical Model - LAN Yuxi; ZHANG Yin; NONG Zhenchang; WEI Yongjiang (Renmin Zhujiang)
Accurate medium and long-term runoff forecast is of great guiding significance to the development and utilization of water resources,allocation optimization,and water dispatch.Based on the three statistical models of mean generating function,periodic analysis,and multiple stepwise regression,this paper studied the medium and long-term runoff forecast of the Longtan Reservoir in the upper reaches of the Xijiang River and the Wuzhou hydrological station in the lower reaches from October to March of the following year and during the entire dry season (six months,from October to March of the following year).The results show that the three models all present positive forecast results.In the calibration and verification periods,the average pass rate exceeds 75%,and the mean absolute percentage error is basically within 30%.The forecast accuracy of the mean generating function and the multiple stepwise regression is significantly higher than that of the periodic analysis,with smaller forecast errors in larger values.Multiple stepwise regression is more stable than the other two models.Furthermore,affected by the consistency of data,the forecast accuracy of the Longtan Reservoir is significantly higher than that of the Wuzhou hydrological station.On the whole,multiple stepwise regression has the optimal forecast effect in the Xijiang River Basin.In addition,it can maintain high forecast accuracy at all levels and stages and provide a valuable reference for water dispatch decisions in the basin.In the future,multi-model fusion can be used to further improve the forecast effect.